PENGARUH PEMBERIAN PENYULUHAN TERHADAP PENGETAHUAN TENTANG PENCEGAHANS TUNTING PADA CALON PENGANTIN - Ika Dhiya Ulhaq; Herlin Fitriana Kurniawati (Institut Citra Internasional, 2025)
Stunting is a significant issue as it adversely impacts the quality of Human Resources (HR). Prospective brides and grooms should get counselling on stunting prevention to enhance their understanding of the significance of nutrition and health before and during pregnancy, which contributes to stunting prevention. This study aims to determine the impact of counselling on the awareness of stunting prevention among prospective brides and grooms. This research was performed in the KUA (Religious Affairs Office) Kapanewon Godean, Sleman Regency, Special Region of Yogyakarta. This study employed a pre-experimental design utilising a one-group pretest-posttest design. This study was carried out in January 2025. The sampling method employed was total sampling with 30 respondents. The findings of this study showed a significant improvement in the knowledge levels of prospective brides and grooms following the intervention, with the majority of respondents classified in the good knowledge category, achieving a posttest score of 96.7%. The Wilcoxon test obtained p = 0.000 (<0.05), indicating that the disparity between the mean pretest and posttest values was statistically significant. Therefore, it may be inferred that counselling significantly impacts the awareness of prospective brides and grooms on stunting prevention. Thus, the findings of this study suggest that stunting counselling for prospective brides and grooms at the KUA should be conducted regularly and consistently.